Athletes', parents', and siblings' experiences from the Special Olympics World Games. Issue Volume 40:Issue2(2015) (3rd April 2015) - Werner, Shirli
Abstract: Background Research supports the importance of sports for people with intellectual disability (ID); however, the unique experience of the Special Olympics (SO) World Games has rarely been examined. The aim of this study was to examine how the SO World Games have affected athletes with ID, their parents and siblings, and the relations between their family members. Method Twenty-three semistructured interviews were conducted with athletes, parents, and siblings within 9 families upon their return from the World Games held in Athens in 2011. Data were analysed using thematic analysis. Results Four themes were found. The first theme dealt with the World Games' role in developing the athletes' self-identity. The second theme related to the World Games' positive impact on their family's quality of life. The third theme related to the World Games' positive impact on siblings, and the fourth theme related to the importance of participation in the World Games in improving community awareness and inclusion for the 3 groups: athletes, parents, and siblings. Conclusions The results are discussed and practical implications are highlighted, including the need to increase knowledge and awareness of the SO.